Basic Tools and Frameworks for Analyzing and Understanding Competitiveness Within the Industry. - Pulaj (Brakaj), Enida; Kume, Vasilika (European Journal of Sustainable Development, 2014)
The relationship between competition and challenges for sustainable growth in the country, industry or a firm is an argument and a basic element for the development of policies, strategies and adaptation to strategic changes. The purpose of this paper is to review the existing frameworks for analysing and understanding competitiveness and especially their application within an industry. In order that, this initiative to study and measure the attractiveness of the industry, to develop and find the proper implementation, it is necessary to build the field and infrastructure through which it will be possible to understand and measure indicators such as attractiveness, rivalry among firms, competitive position in the industry and the strategic choices. Based on this review, it is given the way in which each industry can be studied and, above all, to test the extent of application of the model and the theory of Porter in the Albanian business environment. Key words: competitivenes, industry, strategy, Porter`s forces